2021
DOI: 10.1177/2284026521993680
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dysmenorrhea, its association with overall academic engagement, and management among nursing undergraduates at Peradeniya University, Sri Lanka: A cross-sectional study

Abstract: Background: Dysmenorrhea or painful menstrual periods is one of the common health issues the female university students experience which intervenes with academic activities and quality of life. Objectives: We aimed to find the prevalence, intensity, extent of impairment in academic engagement, and efficacy of the management of dysmenorrhea among nursing students at Peradeniya University, Sri Lanka. Methodology: This cross sectional study comprised 86 female nursing students who represented all four academic ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…-All completed sheet have been reviewed by the researchers. It was found that (262) students were complained from dysmenorrhea with moderate and severe intensity that corresponds well to the characteristics of primary dysmenorrhea indicated in the recent literature review (1,8,9,18) . -A simple random technique was used in this study to ensured obtaining a represented sample of first year faculty nursing students.…”
Section: The Study Was Conducted As Follow: I-assessment and Planning...supporting
confidence: 76%
See 3 more Smart Citations
“…-All completed sheet have been reviewed by the researchers. It was found that (262) students were complained from dysmenorrhea with moderate and severe intensity that corresponds well to the characteristics of primary dysmenorrhea indicated in the recent literature review (1,8,9,18) . -A simple random technique was used in this study to ensured obtaining a represented sample of first year faculty nursing students.…”
Section: The Study Was Conducted As Follow: I-assessment and Planning...supporting
confidence: 76%
“…To achieve the aim of the study the following two tools were used for data collection: Tool (I): Self-administered sheet: This tool was developed by the researchers after reviewing of the related literature (1,8,9,18) . and was used to collect basic data about the students.…”
Section: Iv-tools Of Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations